2010
DOI: 10.1002/eat.20744
|View full text |Cite
|
Sign up to set email alerts
|

Mobile therapy: Use of text‐messaging in the treatment of bulimia nervosa

Abstract: Given the frequent use of mobile phones and text-messaging globally, this proof-of-principle study suggests their use may enhance self-monitoring and treatment for BN leading to improved attendance, adherence, engagement in treatment, and remission from the disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 94 publications
(99 citation statements)
references
References 55 publications
0
95
0
4
Order By: Relevance
“…Mobile devices are ideal to deliver such add-ons as they reach patients in their everyday lives and in the time between treatment sessions. 32,33 For example, Shapiro et al 34 developed and piloted a self-monitoring tool for patients with bulimia nervosa based on text messaging. While undergoing a 12-weeks face-to-face CBT group program, patients submitted daily information on the number of binge eating and purging episodes and on their urges to binge and purge.…”
Section: Harnessing the Power Of Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Mobile devices are ideal to deliver such add-ons as they reach patients in their everyday lives and in the time between treatment sessions. 32,33 For example, Shapiro et al 34 developed and piloted a self-monitoring tool for patients with bulimia nervosa based on text messaging. While undergoing a 12-weeks face-to-face CBT group program, patients submitted daily information on the number of binge eating and purging episodes and on their urges to binge and purge.…”
Section: Harnessing the Power Of Technologymentioning
confidence: 99%
“…The findings indicate good acceptability of the monitoring and feedback system and good adherence to self-monitoring (87% of participants). 34 Controlled studies are needed to investigate whether mobile interventions may actually help to improve patients' adherence to treatment protocols (e.g., compliance with homework assignments, skills training between treatment sessions, reduction of dropout from faceto-face treatment) and ultimately improve the outcome of evidence-based care.…”
Section: Harnessing the Power Of Technologymentioning
confidence: 99%
“…The results are held on a database and as such the therapist can have a recording of the diary entry and when it was made. A study by Shapiro et al (2010) randomized children and adolescents with obesity to three groups: the first group used paper diaries; the second used an electronic diary from their mobile phone and a control group. The participants that used texting versus a paper diary to report on eating behavior demonstrated a lower attrition and greater adherence to the self-monitoring regime.…”
Section: Mobile Phonesmentioning
confidence: 99%
“…Application of new information technologies has shown promise in the treatment of eating disorders. Preliminary studies have found good treatment acceptability in the use of the Internet and text messaging for bulimia nervosa and binge eating disorder (Bauer, Hagel, Okon, Meermann, & Kordy, 2006;Bauer, Percevic, Okon, Meermann, & Kordy, 2003;Shapiro et al, 2007;Shapiro et al, 2010). Adequately powered clinical trials that include the use of email, the Internet, personal digital assistants, text messaging, and other technological advances to enhance treatment will add to future treatment development and should be the next steps for testing technological approaches.…”
Section: Future Research Needsmentioning
confidence: 99%